Plato's Apology the life and teaching of Socrates. - Adler, Mortimer Jerome, 1902-; Encyclopaedia Britannica Educational Corporation (Chicago, IL : Encyclopaedia Britannica Educational Corp., 1962)
Mortimer J. Adler introduces Socrates first as a man who perplexed, inspired, and enraged his fellow citizens; then as a teacher who revolutionized the concept of the teacher's role; and finally, as a philosopher who disturbed the complacency of men's minds for all times.
VHS format.
Narrator, Mortimer J. Adler.
Keywords: Socrates; Plato